Application of anion‐exchange imidazolium silica for the multiphase dispersive extraction of phenolic acids. Issue 16 (17th July 2013) - Bi, Wentao; Row, Kyung Ho
<x xml:space="preserve">Abstract</x> This paper reports the application of a multiphase dispersive extraction method to the extraction, separation, and determination of the phenolic acids from Salicornia herbacea L. using silica‐confined ionic liquids as sorbents. A suitable sorbent for phenolic acid extraction and separation was first identified based on the adsorption behavior of the phenolic acids on different silica‐confined ionic liquids. The sample was then mixed with the optimized sorbent and solvent to achieve multiphase dispersive extraction. The sample/sorbent ratio was optimized using theoretical calculations from the adsorption isotherm and experiments. After transferring the supernatant to an empty cartridge, an SPE process was used to separate the three phenolic acids from the other interference. Through systematic optimization, the optimal conditions produced high recovery rates of protocatechuic acid (91.20%), caffeic acid (94.03%), and ferulic acid (91.33%). Overall, the proposed method is expected to have wide applicability.